Gore Cardioform ASD device thrombus weeks after COVID‐19 infection. Issue 4 (11th January 2022) - Aquino, Liliam; Muniz, Juan Carlos; Laufer, Pablo Marcelo; Prieto, Lourdes R.
Abstract: Device‐related thrombosis and device‐related endocarditis after atrial septal defect (ASD) transcatheter closure are extremely rare. It is known that COVID‐19 infection could lead to a thrombotic microangiopathy‐like phenomenon. We present the case of a 14‐year‐old female who developed fever and was found to have a thrombus on the right atrial side of the ASD closure device weeks after an asymptomatic COVID‐19 infection and negative COVID‐19 test 2 days before transcatheter ASD closure. Although there is no certainty that the thrombus was related to the prior COVID‐19 infection, the possibility of an ongoing COVID‐19‐related hypercoagulable state should be entertained.